Phonology: anthology of dialogue: a visual exploration of dialogue - Atutubo, Kayla Anne; Bennett, Erin; Boyd, Brett; Dehghannegad, Yasmin; Hachi, Sabrine; Harrison, Chloe; Hildebrandt, Riley; Kuling, Brynn; Lafrance, Dominic; McGregor, Carissa; McMullin, Shae; Moniz, Joe; et al. (My University, 2019)
Phonology: A Visual Exploration of Dialogue in Literature, is a project of DESN330 Typography II, a course in the Bachelor of Design at MacEwan University, taught by Assistant Professor Constanza Pacher (MDes). In this experimental typography project, students visually translated an assigned short story into a two-page layout that challenges convention. With the overall goal of enhancing the meaning of the written text through visual devices, students focused on the nuances of language and speech in dialogues. The project encouraged students to explore alternative ways to organize the page, all while maintaining the legibility and readability of the texts. The resulting piece is a collective publication, which was professionally printed in January of 2020. In addition to designing their own spreads, a group of volunteers worked together in conceiving the name of the publication, as well as designing covers, and front and back matter.
Keywords: typography; book design